Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Siswa pada Materi Wujud Zat (IPAS) Kelas IV SDIT Bunayya - Sumiyati, Sumiyati; Nurhikmah, Nurhikmah; Sukrisno, Sukrisno; Paramastuti, Lujeng; Juningsih, Adha (Medan Resource Center, 2023)
This study aimed to assess the effectiveness of the Problem Based Learning (PBL) model in enhancing learning outcomes among fourth-grade students at SD IT BUNAYYA, particularly in the subject of form of substances (IPAS). Conducted through classroom action research (PTK) over three cycles, data was collected via observation and tests. The subjects were fourth-grade students, and success was defined as achieving a class average of at least 7.5. Results showed an average score of 6.4 in cycle I, 6.8 in cycle II, and 8.5 in cycle III, indicating a notable improvement in student learning outcomes. Increased learning activity was also observed. Recommendations include implementing the PBL model in teaching form of substances and fostering students' problem-solving skills through discussion. This research benefits students by enhancing learning outcomes, supports teachers in improving teaching quality, and contributes positively to overall school efforts to enhance student performance.